Bleeding and mortality risk in patients implanted with mechanical prosthetic heart valves with and without thrombocytopenia. Insights from the nationwide PLECTRUM registry. (3rd October 2022) - Menichelli, Danilo; Poli, Daniela; Antonucci, Emilia; Biccirè, Flavio Giuseppe; Palareti, Gualtiero; Pignatelli, Pasquale; Pastori, Daniele
Abstract: Previous studies showed that mechanical prosthetic heart valve (MPHV) patients may develop thrombocytopenia, but its association with clinical outcomes has not been investigated. We enrolled 1, 663 patients with available platelet count from the multicenter nationwide retrospective PLECTRUM registry to investigate the association of thrombocytopenia with all-cause mortality and major bleeding (MB) in patients implanted with MPHV. Thrombocytopenia was defined by platelet count <150 × 10 9 /L. Overall, 44.9% of patients were women and the mean age was 56.7 years. At baseline, 184 (11.1%) patients had thrombocytopenia. Patients with thrombocytopenia were more frequently men and elderly. Platelet count showed an age-dependent decline in men but not in women. We found an increased risk of death in patients with age ≥ 65 years, with a low anticoagulation quality, concomitant arterial hypertension, heart failure, a higher INR range, or with thrombocytopenia (OR 1.739, 95%CI 1.048–2.886, p = .032). At multivariable logistic regression, patients with age ≥65 years, concomitant AF and thrombocytopenia (OR 1.907, 95%CI 1.219–2.983, p = .005) had an increased risk of MBs. In MPHV patients, thrombocytopenia is associated with an increased risk of death and MB. There is a growing need for a sex- and age-specific threshold to define platelet count in adult patients.